Adapting COVID-19 research infrastructure to capture influenza and RSV alongside SARS-CoV-2 in UK healthcare workers winter 2022/23: Evaluation of the SIREN Winter Pressures pilot study. - Sophie Russell; Katie Munro; Sarah Foulkes; Jonathan Broad; Dominic Sparkes; Ana Atti; Jasmin Islam; Susan Hopkins; Victoria Hall; SIREN study group (PLoS ONE)
Background In winter 2022, SIREN, a prospective healthcare worker cohort study monitoring SARS-CoV-2, ran a pilot sub-study introducing multiplex PCR testing for SARS-CoV-2, influenza, and RSV to investigate winter pressures. Three pathways were trialled: (A) on-site (at hospital) swabbing for PCR testing, using the local laboratory for testing, (B) on-site swabbing using a UKHSA-commissioned laboratory for testing, and (C) postal swabbing using a UKHSA-commissioned laboratory for testing. Here, we compare pathways in relation to recruitment, testing coverage, participant acceptability, and UKHSA SIREN research team feedback. Methods A mixed methods evaluation using metrics of quality assurance and study fidelity (participant recruitment and retention; multiplex PCR testing timing and coverage), an adapted NIHR 'participant in research' feedback questionnaire, and thematic analysis of a UKHSA SIREN research team workshop. Results With 7,774 participants recruited, target recruitment (N = 7,500) was achieved. Thirty-nine sites took part in the sub-study (4,289 participants). Thirty-three used pathway A (3,713 participants), and six used pathway B (576 participants). 3,485 participants were enrolled into pathway C (27.8% of invitees). The median number of tests per participant was similar across pathways (6; 4; 5). However, sites using local laboratories showed a wide variation in the date they switched to multiplex testing (28th November 2022-16th March 2023). Consequently, influenza and RSV testing coverage was higher for pathways using UKHSA-commissioned laboratories (100.0% vs 45.6% at local laboratories). 1,204/7,774 (15.5%) participants completed the feedback survey. All pathways were acceptable to participants; 98.9% of postal and 97.5% of site-based participants 'would consider taking part again'. Conclusion Transitioning SARS-CoV-2 PCR testing to include influenza and RSV was challenging to achieve rapidly across multiple sites. The postal testing pathway proved more agile, and UKHSA-commissioned laboratory testing provided more comprehensive data collection than local laboratory testing. This sub-study indicates that postal protocols are effective, adaptable at pace, and acceptable to participants.